PEMBUATAN GAME ZOMBIE SHOOTER BERBASIS ANDROID MENGGUNAKAN UNITY 3D - Agus Hendrah Roni; Darius Andana Haris; Tony Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
Zombie Shooter is a game with a dual-stick shooter genre, sub-genre of action games. Dual-stick shooter is a game that implements virtual thumbstick to control player character. The game designed using Unity 5.2.0 with C# and JavaScript languages. The 3D graphics and components are designed using Blender 2.73a. The camera angle in the game is using isometric camera. Player must survive and complete the mission while zombie come and attack the player. The player must complete the mission before the time out.This game was tested by using blackbox testing method, alpha testing method, and beta testing method. The results indicate that Zombie Shooter can entertain the players because this game is packed in 3D graphics, can be played anywhere (portable), and have a range of different missions.